Determinants of solar technology adoption in rural households: The case of Belesa districts, Amhara region of Ethiopia - Yasin Ahmed; Seid Ebrahim; Mohammed Ahmed (Cogent Economics & Finance, 2022)
The adoption of modern energy such as solar energy has been recognized as, an important way to reduce carbon emissions and enrich the energy supply of rural households in Ethiopia. This study investigated the factors that determine the solar technology adoption in rural households in case of West Belesa and East Belesa districts of Ethiopia. Data were collected from 500 farm households which were selected using a multi-stage sampling technique procedure through a structured survey questionnaire with online KOBO application through the Computer-Assisted-Personal-Interview (CAPI) system. The data was collected through focus group discussions and key informant interviews. Binary logit models were utilize to analyze the data. The finding of the study revealed that seven independent variables were significant in explaining the factors affecting farmers' adoption of solar technology. These variables were education status, family size, participation in natural resource management activity, extension services, knowledge about solar technology, credit utilization, and perception of climatic change were the positive determinants of adoption. Based on the finding, the study recommends that the government should raise farmers' awareness through increase access of education and improved especially credit services to rural household's to increase the adoption of solar energy technology.
Keywords: 330; Solar energy; adoption; determinates; rural households; Ethiopia